The Clinical Efficacy and Safety of Ertapenem for the Treatment of Complicated Urinary Tract Infections Caused by ESBL-Producing Bacteria in Children - KEPENEKLİ KADAYİFCİ, EDA; YAKUT, NURHAYAT (HINDAWI LTD, 2015)
Background. Urinary tract infections (UTIs) are common and important clinical problem in childhood, and extended-spectrumbeta- lactamase- (ESBL-) producing organisms are the leading cause of healthcare-related UTIs. In this study, we aimed to evaluate the clinical efficacy and safety of ertapenem therapy in children with complicated UTIs caused by ESBL-producing organisms. Methods. Seventy-seven children with complicated UTIs caused by ESBL-producing organisms were included in this retrospective study, and all had been treated with ertapenem between January 2013 and June 2014. Results. Sixty-one (79%) females and sixteen (21%) males with amean +/- standard deviation (SD) age of 76.6 +/- 52 months (range 3-204, median 72 months) were enrolled in this study. Escherichia coli (E. coli) (n = 67; 87%) was the most common bacterial cause of the UTIs followed by Klebsiella pneumoniae (K. pneumoniae) (n = 9; 11.7%) and Enterobacter cloacae (E. cloacae) (n = 1; 1.3%). The mean duration of the ertapenem therapy was 8.9 +/- 1.6 days (range 4-11). No serious drug-related clinical or laboratory adverse effects were observed, and the ertapenem therapy was found to be safe and well tolerated in the children in our study. Conclusion. Ertapenem is a newer carbapenem with the advantage of once-daily dosing and is highly effective for treating UTIs caused by ESBL-producing microorganisms.
Keywords: RISK-FACTORS